Pengaruh Iklan, Promosi Dan Review Produk Lipcream Makeover Terhadap Keputusan Pembelian Di Shopee - Fauziah, Nur Assyifa; Zed, Etty Zuliawati (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to see the influence of advertising, promotions and reviews of Lipcream MakeOver products on shopee on purchasing decisions. This research was conducted to understand the factors that influence consumers in deciding to by cosmetic product on shopee. The research method used is quantitative. With the population of people who have purchased Lipcream MakeOver product. Data collection includes distributing questionnaires. The data analysis method used is the reliability test, realibility test, classical assumption test, multiple linear regression test and hypothesis test. The research results show that advertising, promotions and product review have a significant positive influence on consumer purchasing decisions. Advertisements and product promotions on Shopee can increase consumer interest in purchasing Lipcream MakeOver, while product reviews from previous buyers also have a positive influence on purchasing decisions. These findings have important implications for cosmetic manufactures and sellers on Shopee in designing effective marketing strategies to increase sales of their products.